In Vivo Differentiation of Aerobic Brain Abscesses and Necrotic Glioblastomas Multiforme Using Proton MR Spectroscopic Imaging - Lai, P.H.; Weng, H.H.; Chen, C.Y.; Hsu, S.S.; Ding, S.; Ko, C.W.; Fu, J.H.; Liang, H.L.; Chen, K.H. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Abscesses caused by aerobic bacteria (aerobic abscesses) can simulate intracranial glioblastomas multiforme (GBMs) in MR imaging appearance and single voxel (SV) proton MR spectroscopy of the central cavity. The purpose of our study was to determine whether MR spectroscopic imaging (SI) can be used to differentiate aerobic abscesses from GBMs. Our hypothesis was that metabolite levels of choline (Cho) are decreased in the ring-enhancing portion of abscesses compared with GBMs.MATERIALS AND METHODS: Fifteen patients with aerobic abscesses were studied on a 1.5T MR scanner using an SV method and an SI method. Proton MR spectra of 15 GBMs with similar conventional MR imaging appearances were used for comparison. The resonance peaks in the cavity, including lactate, cytosolic amino acids, acetate, succinate, and lipids, were analyzed by both SV MR spectroscopy and MRSI. In the contrast-enhancing rim of each lesion, peak areas of N-acetylaspartate (NAA), choline (Cho), lipid and lactate (LL), and creatine (Cr) were measured by MRSI. The peak areas of NAA-n, Cho-n, and Cr-n in the corresponding contralateral normal-appearing (-n) brain were also measured. Maximum Cho/Cr, Cho/NAA, LL/Cr-n, and Cho/Cho-n and minimum Cr/Cr-n and NAA/NAA-n ratios in abscesses and GBMs were compared using the Wilcoxon rank sum test. After receiver operating characteristic curve analysis, diagnostic accuracy was compared.RESULTS: Cytosolic amino acid peaks were found in the cavity in 7 of 15 patients with aerobic abscesses. Means and SDs of maximum Cho/Cr, Cho/NAA, LL/Cr-n, and Cho/Cho-n and minimum Cr/Cr-n and NAA/NAA-n ratios were 3.38 ± 1.09, 3.88 ± 2.13, 2.72 ± 1.45, 1.98 ± 0.53, 0.53 ± 0.16, and 0.44 ± 0.09, respectively, in the GBMs, and 1.77 ± 0.49, 1.48 ± 0.51, 2.11 ± 0.67, 0.81 ± 0.21, 0.48 ± 0.2, and 0.5 ± 0.15, respectively, in the abscesses. Significant differences were found in the maximum Cho/Cr (P = .001), Cho/NAA (P = .006), and Cho/Cho-n ratios (P < .001) between abscesses and GBMs. Diagnostic accuracy was higher by Cho/Cho-n ratio than Cho/Cr and Cho/NAA ratios (93.3% versus 86.7% and 76.7%).CONCLUSION: Metabolite ratios and maximum Cho/Cho-n, Cho/Cr, and Cho/NAA ratios of the contrast-enhancing rim were significantly different and useful in differentiating aerobic abscesses from GBMs by MRSI.